Effectiveness of virtual laboratory vs. paper-based experiences to the hands-on chemistry practical in Tanzanian secondary schools - Manyilizu, Majuto Clement (Education and information technologies, 2023)
Science subjects at pre-tertiary and tertiary education levels are important for socio-economic and industrial development of any country; however, they are difficult for students to construct their concepts. In Tanzania, insufficient or lack of practical experiments are major challenges for science subjects due to insufficient or lack of laboratories, apparatus, expertise or reagents. Thus, this research assesses the effectiveness of paper-based against virtual laboratory experiences towards improvement of real (hands-on) chemistry practical in Tanzanian secondary schools focusing in Dodoma region. Chemistry virtual laboratory was developed and being deployed at Dodoma Secondary School for students who were never done practical sessions before to avoid biasness towards the study. The students were divided into three groups, namely paper-based and real laboratory as control groups (CG) and virtual laboratory as the experiment group (EG). Each group was further divided into two groups for the rest approaches forming six (6) groups. For EG, students were taught based on instructional approach which was enriched by computer animations in the computer laboratory. Results indicate that students who firstly attended virtual laboratory performed better in real laboratory than those who firstly attended real laboratory. Furthermore, the best progressive learning and performance for real experiments appears when the virtual laboratory preceded paper-based practical experiments. Thus, virtual laboratory is a very useful tool for learning chemistry practical not only to schools without laboratories but also to those with laboratories; and it should be considered by all the pre-tertiary schools in Tanzania and other schools in similar situations.